Large Animal Models of Vascularized Composite Allotransplantation: A Review of Immune Strategies to Improve Allograft Outcomes - Matar, Abraham J.; Crepeau, Rebecca L.; Mundinger, Gerhard S.; Cetrulo, Curtis L.; Torabi, Radbeh (Frontiers in Immunology, 2021)
Over the past twenty years, great technical strides have been made in the area of vascularized composite tissue allotransplantation (VCA). As in solid organ transplantation, the allogeneic immune response remains a significant barrier to long term VCA survival and function. Strategies to overcome acute and chronic rejection, minimize immunosuppression and prolong VCA survival have important clinical implications. Historically, large animals have provided a valuable model for testing the clinical translatability of immune modulating approaches in transplantation, including tolerance induction, co-stimulation blockade, cellular therapies, and ex vivo perfusion. Recently, significant advancements have been made in these arenas utilizing large animal VCA models. In this comprehensive review, we will highlight recent immune strategies undertaken to improve VCA outcomes with a focus on relevant preclinical large animal models.